Response to HER2 Inhibition in a Patient With Brain Metastasis With EGFR TKI Acquired Resistance and an HER2 Amplification - Meedendorp, Arenda D.; ter Elst, Arja; ’t Hart, Nils A.; Groen, Harry J. M.; Schuuring, Ed; van der Wekken, Anthonie J. (Frontiers in Oncology, 2018)
A 62-year old man was referred to our university hospital for treatment of advanced adenocarcinoma of the lung after disease progression on two lines of EGFR-TKI and one line of chemotherapy. FISH analysis upon progression showed a HER2 amplification. At our weekly Molecular Tumour Board (MTB) a decision was made to treat this patient with afatinib, which resulted in a partial response. However, progression was observed with a facial nerve paresis due to a metastasis in the skull. A biopsy of a location in the thorax revealed the presence of a EGFR-T790M mutation associated with acquired resistance, after which treatment with osimertinib was started. After 6 months, disease progression was observed and a new biopsy was taken from the pelvic bone, which revealed the original amplification of HER2 together with the EGFR-L858R mutation, the EGFR-T790M mutation was not detected. The MTB decided to treat the patient with trastuzumab/paclitaxel. A partial response was observed in different bone lesions, while the skull metastasis with ingrowth in the brain remained stable for 6 months. Because of progression of the bone metastases after 6 months, a biopsy of a lesion in the thorax wall was taken. In this lesion the EGFR-T790M mutation could be detected again. The MTB advised to start treatment with a combination of osimertinib and afatinib. This resulted in an impressive clinical improvement and a partial response of the bone metastases on the most recent 18-FDG-PET-CT-scan. Conclusion: Adjusting treatment to the mutational make-up of the tumour is a great challenge. For optimal treatment response multiple biopsies and re-biopsy upon progression are imperative. As more genes are investigated, treatment decision becomes increasingly difficult, therefore, expert opinions from a MTB is essential. Conclusion: Adjusting treatment to the mutational make-up of the tumour is a great challenge. For optimal treatment response multiple biopsies and re-biopsy upon progression are imperative. As more genes are investigated, treatment decision becomes increasingly difficult, therefore, expert opinions from a MTB is essential.